Comparison of Two Types of Endothelial Cells in Long Term Culture - Sedlak, Bonnie Joy; Booyse, F. M; Bell, S; Rafelson, M. E, Jr. (Thrombosis and Haemostasis, 1976)
Bovine aortic endothelial cells have been serially subcultured and maintained for ten months (24 passages) without any apparent loss of endothelial-like properties. There appear to be two endothelial cell types; one type is mononucleated, 40—60 μ in diameter, and the other (giant) cell type, multinucleate and 300-600 μ in diameter. Both cell types were identified as endothelial cells by established criteria; 1. ultrastructurally, by the presence of Weibel-Palade bodies, microfilaments and pinocytotic vesicles and 2. immunologically, by the presence of factor VIII antigen and thrombosthenin.